Analysis of Total Suspended Matter and Chlorophyll-a Distribution In Prigi Coastal Area using Remote Sensing - Zakiyah, Umi; Darmawan, Arief; Lazuardi, Dian Senja (Faculty of Fisheries and Marine, Universitas Riau, 2020)
Total Suspended Matter (TSM) and chlorophyll-a are water quality parameters which can be mapped using remote sensing. High TSM values could affect chlorophyll-a in phytoplankton for photosynthesis. The aims of this research were to analyze distribution, accuracy, and relationship between TSM and chlorophyll-a based on the imagery and in situ data in Prigi Coastal waters. The method that used in this research was descriptive. The data used was Landsat 8 imagery that captured on May, 20th 2018 and in situ samples taken using purposive sampling technique in 9 locations on May, 19th 2018. From the results of this research, TSM in situ value ranged from 41-64 ppm and imagery value ranged from 44-65 ppm, chlorophyll-a in situ value ranged from 1.15-2.68 mg/m3, and imagery value ranged from 1.24-2.41 mg/m3. From the results of in situ and imagery data obtained the accuracy value for TSM 74.37% and for chlorophyll-a 80.33%. The relationship between the TSM and chlorophyll-a value was y= -0.045x + 3.9103 with a coefficient value 85%, which means that the variable X (TSM) affects the variable Y (chlorophyll-a). The conclusion of this study was Prigi Coastal waters had a value at the threshold of each parameters. So, could be classified as good quality of waters. High accuracy between imagery and in situ data shows that remote sensing method was suitable for use in the Prigi coastal waters.